144k views
4 votes
Pleaseeee help thank you!

Pleaseeee help thank you!-example-1

1 Answer

3 votes

Answer:

B

Explanation:

Just a quick note to start with. 2^(n-2) will eventually give 32, (2^5) but n - 2 doesn't go that high (to 5). n would have to be 7 in order to get 32. So C is not the answer.

I think what you are intended to do is find the sum of the terms created by letting n = 1 then 2 then 3 then 4 then 5

n = 1

2^(1 - 2)

2^(-1)

1/2

n = 2

2^(2 - 2)

2^0 and that should give ta da

1.

n= 3

2^(3 -2)

2^(1)

2

n = 4

2^(4 - 2)

2^(2)

4

n = 5

2^(5 - 2)

2^3

8

Now you just add all of them together.

1/2 + 1 + 2 + 4 + 8

15 1/2

15.5

The answer to the summation is 15.5

The Answer is B

User Markthegrea
by
5.3k points